NKT Cells as an Ideal Anti-Tumor Immunotherapeutic - Fujii, Shin-ichiro; Shimizu, Kanako; Okamoto, Yoshitaka; Kunii, Naoki; Nakayama, Toshinori; Motohashi, Shinichiro; Taniguchi, Masaru (Frontiers in Immunology, 2013)
Human NKT cells are characterized by their expression of an invariant T cell antigen receptor (TCR)  chain variable region encoded by a V24J18 rearrangement. These NKT cells recognize -galactosylceramide (-GalCer) in conjunction with the MHC class-I-like CD1d molecule and bridge the innate and acquired immune systems to mediate efficient and augmented immune responses. A prime example of one such function is adjuvant activity: NKT cells augment anti-tumor responses because they can rapidly produce large amounts of IFN-, which acts on NK cells to eliminate MHC negative tumors and also on CD8 cytotoxic T cells to kill MHC positive tumors. Thus, upon administration of -GalCer-pulsed DCs, both MHC negative and positive tumor cells can be effectively eliminated, resulting in complete tumor eradication without tumor recurrence. Clinical trials have been completed in a cohort of 17 patients with advanced non-small cell lung cancers and 10 cases of head and neck tumors. Sixty percent of advanced lung cancer patients with high IFN- production had significantly prolonged median survival times (MST) of 29.3 Mo with only the primary treatment. In the case of head and neck tumors, 10 patients who completed the trial all had stable disease or partial responses 5 wks after the combination therapy of -GalCer-DCs and activated NKT cells. We now focus on two potential powerful treatment options for the future. One is to establish artificial adjuvant vector cells containing tumor mRNA and -GalCer/CD1d. This stimulates host NKT cells followed by DC maturation and NK cell activation but also induces tumor-specific long-term memory CD8 killer T cell responses, suppressing tumor metastasis even one year after the initial single injection. The other approach is to establish induced pluripotent stem (iPS) cells that can generate unlimited numbers of NKT cells with adjuvant activity. Such iPS-derived NKT cells produce IFN- in vitro and in vivo upon stimulation with -GalCer/DCs